Vision of Education of Swami Vivekananda and Swami Dayana: - (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Swami Vivekanandafinds education as the major weapon to fight against all these social as wellas global evils. He realizes that solution of these lies in education,enlightenment. In his vision the spiritual awakening of mankind is mainlyneeded. This constitutes as the main purpose of his philosophy of education.There is only constant attempt to disregard and discard everything that is oldwhich has become a fashion of the day.